Speech intelligibility and its relation to auditory temporal processing in Czech and Swiss German subjects with and without tinnitus - Bureš, Zbyněk; Profant, Oliver; Sommerhalder, Nick; Skarnitzl, Radek; Fuksa, Jakub; Meyer, Martin (European archives of oto-rhino-laryngology, 2024)
PURPOSE: Previous studies have shown that levels for 50% speech intelligibility in quiet and in noise differ for different languages. Here, we aimed to find out whether these differences may relate to different auditory processing of temporal sound features in different languages, and to determine the influence of tinnitus on speech comprehension in different languages. METHODS: We measured speech intelligibility under various conditions (words in quiet, sentences in babble noise, interrupted sentences) along with tone detection thresholds in quiet [PTA] and in noise [PTAnoise], gap detection thresholds [GDT], and detection thresholds for frequency modulation [FMT], and compared them between Czech and Swiss subjects matched in mean age and PTA. RESULTS: The Swiss subjects exhibited higher speech reception thresholds in quiet, higher threshold speech-to-noise ratio, and shallower slope of performance-intensity function for the words in quiet. Importantly, the intelligibility of temporally gated speech was similar in the Czech and Swiss subjects. The PTAnoise, GDT, and FMT were similar in the two groups. The Czech subjects exhibited correlations of the speech tests with GDT and FMT, which was not the case in the Swiss group. Qualitatively, the results of comparisons between the Swiss and Czech populations were not influenced by presence of subjective tinnitus. CONCLUSION: The results support the notion of language-specific differences in speech comprehension which persists also in tinnitus subjects, and indicates different associations with the elementary measures of auditory temporal processing.
Keywords: Language; Auditory Threshold; percepce řeči; Tinnitus; Czech Republic; vnímání času; Humans; Speech Perception; sluchová percepce; Perceptual Masking; lidé; Time Perception; Česká republika; jazyk (prostředek komunikace); sluchový práh; Auditory Perception; srozumitelnost řeči; tinnitus; Speech Intelligibility; Switzerland; Švýcarsko; percepční maskování